THE LEFT TURN OF THE ITALIAN DEMOCRATIC PARTY (PD): PRIMARY ELECTIONS AND POLICY PREFERENCES (Studia Politica. Romanian Political Science Review, 2025)
On February 26, 2023, for the first time in the history of the Democratic Party, the leading Italian progressive party, a woman, Elly Schlein, was elected leader through open primaries that contradicted the outcome of consultations among the membership. Observing the outcome of an exit poll conducted by the Standing Group Candidate and Leader Selection of the Italian Political Science Society focusing on the policy priorities of the electorate, it clearly emerges that the inclusive rules of intra-party democracy, under certain conditions, can impact the identity of the party, leading in this case to a sharp turn to the left.More specifically, the positions of the electorates of the two candidates, Elly Schlein and Stefano Bonaccini, diverge significantly on issues that appear to be crucial for the political positioning of the party.
Keywords: Democratic Party; intra-party democracy; political impact; policy issues; left turn